2002
DOI: 10.1074/jbc.m204405200
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of novH in Adrenocortical Cells Is Down-regulated by TGFβ1 through c-Jun in a Smad-independent Manner

Abstract: The human NOV secreted glycoprotein (NOVH) is abundant in the fetal and adult adrenal cortex. The amount of NOVH increases in benign adrenocortical tumors and decreases in malignant adrenocortical tumors, suggesting that NOVH plays a role in tumorigenesis in the adrenal cortex. Transforming growth factor ␤1 (TGF␤1), fibroblast growth factor 2 (FGF2), and insulin growth factors (IGFs) play crucial roles in the physiology of the adrenal cortex. We investigated the effects of these factors on the expression of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 81 publications
(87 reference statements)
4
28
0
Order By: Relevance
“…Previous studies indicate that AP-1 is critical for TGFβ-mediated reduction of CCN3 expression in adrenocortical cells (NCI H295R) (Lafont et al 2002). In addition, steroidogenic factor-1 (SF-1) has been shown to transcriptionally downregulate CCN3 in NCI H295R cells (Doghman et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that AP-1 is critical for TGFβ-mediated reduction of CCN3 expression in adrenocortical cells (NCI H295R) (Lafont et al 2002). In addition, steroidogenic factor-1 (SF-1) has been shown to transcriptionally downregulate CCN3 in NCI H295R cells (Doghman et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The CCN3 promoter luciferase construct was kindly provided by Dr. C. Martinerie (France) (Lafont et al 2002), this construct was used as template to clone the proximal 492 base pair CCN3 promoter into pGL3-Basic vector (Promega, Madison, WI). CCN3 promoter deletion constructs were generated by PCR.…”
Section: Transient Transfectionmentioning
confidence: 99%
“…CCN2 induces differentiation of myofibroblasts and increased collagen synthesis in concert with EGF, insulin-like growth factor 2 or insulin (Grotendorst et al, 2004;Gore-Hyer et al, 2003). Moreover, although not mitogenic on its own, CCN3 enhances basic-FGF-induced DNA synthesis and upregulates matrix metalloproteinase (MMP)-1 and PAI-1 expression (Lafont et al, 2005a;Lin, C. et al, 2005). In some studies, however, CCN2 has been shown to possess independent yet modest proliferative activity (~20% above control) (Asano et al, 2005).…”
Section: Ccns As Co-factors For the Ecm Growth Factors And Cytokinesmentioning
confidence: 99%
“…Significantly, CCN3 promotes FGF-and PDGF-mediated proliferation of C2C12 myoblast cells in an integrin-dependent fashion (Lafont et al, 2005a). Through integrins, CCN proteins thus probably modify signaling responses to other proteins and, in principle, CCN molecules could modify a wide range of signal transduction pathways.…”
Section: Ccns As Co-factors For the Ecm Growth Factors And Cytokinesmentioning
confidence: 99%
“…lated through the Smad-independent pathways (32,33). To evaluate whether the Smad pathway is involved in the down-regulation of Cited2 by TGF-␤, an expression plasmid for Smad7, an inhibitory Smad, was introduced into MDA-MB-231 cells through retrovirus-mediated gene transfer ( Fig.…”
Section: Tgf-␤ Down-regulates Cited2 In Mda-mb-231 Cells-chen Et Almentioning
confidence: 99%